FAKTOR KEBERHASILAN CAPAIAN KINERJA INSTRUKTUR PELATIHAN KETERAMPILAN TEKNIS PENDATAAN KELUARGA (Studi di Balai Latihan dan Pengembangan Perwakilan BKKBN Provinsi Jawa Barat) - Nilla Nurlaila, - (2022)
The training instructor is the spearhead in the implementation of the training which affects the training output. The training instructor is involved in the planning to evaluation process. This causes the performance of the training instructor to be a trigger for the success of a training. Therefore, the performance of the training instructor is one of the factors that must be considered. The measure of performance achievement of training instructors at the Training and Development Center for the Representatives of the BKKBN of West Java Province refers to the achievements of the program and training guidelines contained in the training curriculum. The purpose of this study was to determine the work program of the technical training of family data collection, the work performance of the training instructor and to analyze the factors that influence the performance of the technical training instructor of family data collection. This study uses a qualitative approach, with a total of 6 informants consisting of a research and development coordinator, training instructors and training participants. The results of the study stated that there were 5 factors that influenced the performance of training instructors, namely personal factors, the implementation of training instructor competencies in the implementation of training. Leadership factor, the support provided by the coordinator in the aspects of self-development and coaching. Team factor, indicated by the existence of an organizational culture in the form of cooperation, kinship and tolerance from colleagues. System factor, the existence of a clear vision and mission, the division of a structured work system and completeness of training facilities and infrastructure. Contextual or situational factors, indicated by the change from offline training to online training. Keywords: training instructor, performance and factors affecting performance